THE IMPROVEMENT OF STUDENTS’ CREATIVITY AND LEARNING OUTCOMES THROUGH SONG MAKING IN YEAR VII-B STUDENTS OF MTsN 1 WEST ACEH - Dahniar Dahniar (Pedagogi: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine "The Improvement of Students’ Creativity and Learning Outcomes through Song Making in Year VII-B Students of MTsN 1 West Aceh ". The sample of this research was the students of Year VII-B, which the total number was 36 students. This study used Classroom Action Research (CAR) with the methods of observation, data collection, tests, documentation and data analysis. This study used two cycles to determine the improvement of students’ creativity and learning outcomes through song making in Year VII-B students of MTsN 1 West Aceh. The results of this study indicated that through making songs, it can improve creativity and learning outcomes of students in Year VII-B of MTsN 1 West Aceh. As for the results, it can be seen from the learning outcomes of the students in the pre-cycle, the first and the second cycles. The students’ learning outcomes in the pre-cycle was only 14 students (38.88%,) who reached the passing grade, in the first cycle, it increased to 26 students (72.22%) and in the second cycle, it was 36 students (100%) reached the passing grade.